THE STYLE FEATURES OF STUDENTS' COGNITIVE ACTIVITY AS THE BASIS FOR FORMATION OF MATHEMATICAL LITERACY - Podkhodova, Natalia; Snegurova, Victoria (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Mathematical literacy is the main indicator of the mathematical development of schoolchildren from different countries. In the concept of the direction "mathematical literacy" of the PISA-2021 study, the key component of the concept of mathematical literacy is mathematical reasoning. The development of this skill, first of all, is determined by the stylistic features of the cognitive activity of students in the study of mathematics. Taking them into account in the development of educational material in mathematics will create optimal conditions for the formation of a key component of mathematical literacy. But there are many stylistic features of cognitive activity. Therefore, to develop optimal conditions, taking into account the style features, it is necessary to answer the question: "Which of the style features of cognitive activity have a stronger effect on the effectiveness of solving mathematical problems and how to implement them in educational mathematical activity." In our study, we identified various ways of implementing style features in educational mathematical material, one of the most significant are ways of presenting (coding) information. With this in mind, an experiment was conducted. We applied analysis of variance to its results. The study showed: 1) in general, it is possible to trace relations between successful mathematical problem solving by students with certain individual styles and the way the selected problem is represented; 2) it is necessary to make further research on students' awareness of their personal cognitive characteristics (style features).